Pengaruh Penerapan Sistem Manajemen Sumber Daya Perusahaan (ERP) dalam Meningkatkan Kinerja Manajemen Rantai Pasok (SCM) AirAsia - Yulfiswandi; Benedicte Hartono; Carol; Jackson; Vina Sonata; Winna Angelina (STEKOM PRESS, 2023)
Superior companies need good management, including supply chain management which must also run well to prevent things that have a negative impact on the company. Good supply chain management provides advantages for companies, one of which is for AirAsia so that valuable resources are needed. This research discusses what the ERP system looks like at AirAsia and how this ERP system can maximize supply chain performance that is currently running. This research uses a type of qualitative research and data analysis was carried out using a qualitative descriptive technique. The conclusion drawn from the results of this research analysis is that the ERP system has succeeded in improving the performance of supply chain management at AirAsia so that it is effective in increasing efficiency in AirAsia's own operations as a low-cost airline with the best quality in the world.